2011
DOI: 10.1017/s1368980011001996
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity among adults residing in disadvantaged urban areas: potential health and dietary consequences

Abstract: Objective: Food insecurity is the limited or uncertain availability or access to nutritionally adequate, culturally appropriate and safe foods. Food insecurity may result in inadequate dietary intakes, overweight or obesity and the development of chronic disease. Internationally, few studies have focused on the range of potential health outcomes related to food insecurity among adults residing in disadvantaged locations and no such Australian studies exist. The objective of the present study was to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
169
5
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(199 citation statements)
references
References 65 publications
17
169
5
7
Order By: Relevance
“…These findings are in accordance with previous studies (2,7,13,17) , which found that food insufficiency or food insecurity was associated with poor general health, increased health-care utilisation and depression. Ding et al (17) reported an association between food insecurity and poor sleep in US adults.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in accordance with previous studies (2,7,13,17) , which found that food insufficiency or food insecurity was associated with poor general health, increased health-care utilisation and depression. Ding et al (17) reported an association between food insecurity and poor sleep in US adults.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with other studies 26,30 , the elderly who reported regular, poor, or very poor health were more likely to be food insecure. According to Ramsey et al 26 , the physiological and psychological changes caused by nutritional deficiencies and the concern caused by restricted access to food may explain the association between food insecurity and many diseases.…”
Section: Daily Not Dailysupporting
confidence: 89%
“…Consistent with other studies 26,30 , the elderly who reported regular, poor, or very poor health were more likely to be food insecure. According to Ramsey et al 26 , the physiological and psychological changes caused by nutritional deficiencies and the concern caused by restricted access to food may explain the association between food insecurity and many diseases. A study conducted in Canada in 1996 with 153 women found that those who had experienced food insecurity in the past twelve months, including the past thirty days, were twice as likely to report activity limitations due to disease or disability 30 .…”
Section: Daily Not Dailysupporting
confidence: 89%
See 1 more Smart Citation
“…For example, the question regarding fruit was as follows: 'How many pieces of fruit do you usually eat per day? (count 1/2 cup of tinned fruit or 1 cup of fresh fruit/berries/grapes or 1/3 cup of dried fruit or 1/2 cup of juice as 1 piece)', with responses as 'don't eat fruit', 'less than 1 piece per day', '1 piece per day', '2 pieces per day', '3 pieces per day' and '4 or more pieces per day'.Survey responses were compared with responses from three other surveyed groups: a (i) representative sample of the Australian population (29) ; (ii) a sample of socioeconomically disadvantaged Brisbane residents (28) ; and Samoans' dietary habits in Australia 789(iii) a migrant Pacific Island population in New Zealand (30) . All four samples were population-based.…”
mentioning
confidence: 99%